Cantar, Dançar e Brincar com as Músicas da Galinha Pintadinha - Xavier , Alda de Souza; Santana , Lusmar Moreira de Azevedo; Botassin, Rosa Maria Ferreira (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf